Algorithms optimization for the image processing and analysis by constructing parallel solutions - Bartyzel, Krzysztof (Studia Informatica. System and information technology, 2019)
This paper presents a concept of parallel programming in the context of image analysis and processing algorithms. It demonstrates an exact implementation of the issue of image filtration using the Microsoft .NET framework and the C# language. All technical aspects were subject to analysis. Presented are both theoretical considerations and nuances of implementation. An experiment was also conducted which consisted in the creation of an appropriate program to demonstrate an example noise filter and the recording of performance time in the case of synchronous and parallel execution. The solution analysis was tested on a typical, average laptop and a server with high computing power. The results unanimously show that applying parallel algorithms can significantly improve the effectiveness of the hardware used.